Protocell Survival Networks in Spatially Modulated Chemical Gradients - Shuqi Wu (582226) (2025)
Coupling molecular-level chemical networks to macroscopic functions provides a step toward the implementation of rudimentary forms of agency in life-like objects and materials. Here, a negative feedback circuit within a networked binary protocell community is linked to higher-level spatial dynamic behaviors by exposing the consortium to a unidirectional reaction-diffusion gradient of an activator. The activator initiates artificial lysis and release of protocell-encapsulated enzymes, which spatiotemporally restrict membrane disassembly to generate distinct protocell survival boundaries within homogeneously distributed or segregated arrangements of the binary populations. We track the collective defense responses under nonequilibrium conditions and show that spatial symmetry breaking is related to the local generation of a hydrogen peroxide gradient and is strongly influenced by confinement and edge effects that spatially modulate the protocell survival networks formed within the hydrogels. In each case, the results are validated by computer simulations based on reaction-diffusion modeling. Overall, our work presents a general approach to implementing and decoding the spatial dynamic behaviors and collective responses of chemically networked protocell communities operating under nonequilibrium conditions and provides a pathway to self-protective cytomimetic systems that exhibit quasi-intelligent spatiotemporal behaviors in response to gradient-mediated activation.